2010
DOI: 10.1177/0272431610379415
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Experiences and Compromised Academic Performance Across Middle School Grades

Abstract: The goal of the study was to examine whether bullying experiences are associated with lower academic performance across middle school among urban students.The ethnically diverse sample was drawn from a longitudinal study of 2,300 sixth graders (44% Latino, 26% African American, 10% Asian, 10% White, and 10% mixed) from 11 public middle schools. Results of multilevel models (MLMs) showed that grade point averages and teacher-rated academic engagement were each predicted by both self-perceptions of victimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
204
5
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(225 citation statements)
references
References 24 publications
(29 reference statements)
10
204
5
6
Order By: Relevance
“…Students at the base of the official hierarchy tend to be either perpetrators or victims of school violence, but especially perpetrators. The studies conducted by Juvonen et al (2011), Mehta et al (2013), and Strøm et al (2013) confirm this study's results, that academic performance is inversely related to school violence. As these students are considered unpopular, they perhaps perceive aggression directed to their equals and to those with a poor performance in physical education to be an opportunity to stand out and become popular.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Students at the base of the official hierarchy tend to be either perpetrators or victims of school violence, but especially perpetrators. The studies conducted by Juvonen et al (2011), Mehta et al (2013), and Strøm et al (2013) confirm this study's results, that academic performance is inversely related to school violence. As these students are considered unpopular, they perhaps perceive aggression directed to their equals and to those with a poor performance in physical education to be an opportunity to stand out and become popular.…”
Section: Discussionsupporting
confidence: 83%
“…The fact that there is a relationship between being perceived by peers to be a victim and considering oneself as such, but there is no relationship between being considered by peers or considering oneself to be an abuser, may suggest that victims are more sensitive to aggression that they experience than abusers are to aggression they practice; perhaps, abusers consider aggression to be just a joke while victims do not. The study conducted by Juvonen et al (2011) also found a low correlation between peer perception and self-reporting of abuser or victim. These results suggest that studies addressing school violence do not only employ the individuals' selfreport since peer perception seems to be more accurate: various students provide their perceptions.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Specifically, researchers have documented that victimized children are at risk for psychosocial problems including loneliness, low self-esteem and poor social relationships (Ladd & Troop-Gordon, 2003) as well as suicide, suicidal ideation and nonsuicidal self-injury (Bonanno & Hymel, 2010;Heilbron & Prinstein, 2010;Klomek, Marrocco, Kleinman, Schonfeld, & Gould, 2007). Further, bullied children tend to underperform academically (Juvonen, Wang, & Espinoza, 2011) and exhibit avoidant behaviors, such as developing negative school attitudes (Kochenderfer & Ladd, 1996a, 1996b, truancy, absenteeism and dropping out (Otieno & Choongo, 2010).…”
Section: To Tell or Not To Tellmentioning
confidence: 99%